The Bond of Mother and Child in the Lyrics of the Song Linked by Nadin Amizah (Semiotic Analysis of Roland Barthes) - Mutiara Umami Ningsih Mutiara; Muhammad Alfikri Matondang (Dinasti International Journal of Education Management And Social Science, 2024)
Music is a creative medium that people use to communicate their emotions and worldview. Through song lyrics and accompanying video clips, someone uses music to express opinions, feelings, or even social criticism. 'Bertaut' by Nadin Amizah is a song about someone's outpouring of emotions which has succeeded in capturing the audience's attention and winning various awards. Even though it was released a year ago, "Bertaut" still tops the charts on music platforms to this day. Using Roland Barthes' semiotics, this research seeks to identify and examine the mother-child bond that appears in the song "Bertaut" by Nadin Amizah. This research was analyzed semiotically using Roland Barthes' semiotics and is qualitative descriptive with a critical paradigm. The author conducted library research to collect information by looking through books, news, articles and other literary works. The information is then recorded and recorded. The findings of this research clarify the myths, connotations and denotations regarding the mother-child bond contained in the song "Bertaut" by Nadin Amizah. This song tells the story of the difficulties a single mother faces in supporting her family and herself. Family members assign responsibilities to each other, and they are each responsible for their own duties.